The Global Sanctions Data Base – Release 3: Covid-19, Russia, and Multilateral Sanctions - Constantinos Syropoulos; Gabriel J. Felbermayr; Aleksandra Kirilakha; Erdal Yalcin; Yoto V. Yotov (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper introduces the third update/release of the Global Sanctions Data Base (GSDB-R3). The GSDB-R3 extends the period of coverage from 1950-2019 to 1950-2022, which includes two special periods – COVID-19 and the war between Russia and Ukraine. The new update of the GSDB contains a total of 1,325 cases. In response to multiple inquiries and requests, the GSDB-R3 has been amended with a new variable that distinguishes between unilateral and multilateral sanctions. As before, the GSDB comes in two versions, case-specific and dyadic, which are freely available upon request at GSDB@drexel.edu. To highlight one of the new features of the GSDB, we estimate the heterogeneous effects of unilateral and multilateral sanctions on trade. We also obtain estimates of the effects on trade of the 2014 sanctions on Russia,
Keywords: F10; F13; F14; F50; F51; H50; N40; 330; sanctions; Covid; Russia; multilateral sanctions; unilateral sanctions